How Do Organizational Factors Shape Employee Engagement? A Systematic Review of Empirical Evidence and Theoretical Perspectives - Anapah, Maria Goreti Ilmiana; Al Musadieq, Mochammad; Ruhana, Ika (FIA UB, 2026)
The problem of low employee engagement in the workplace has been identified both globally and nationally. Empirical research on employee engagement has increased in recent years. However, independent survey organizations such as Gallup continue to identify low employee engagement, underscoring the urgency of addressing the problem through a systematic analysis of the growing literature. This study aims to analyze previous research to confirm its fragmented contributions and identify gaps for future research that are more relevant to the evolving workplace environment. The literature analysis, collected from Scopus and Web of Science databases, was then screened using inclusion and exclusion criteria to ensure only high-quality articles focused on employee engagement were used. The screening process resulted in 34 selected articles. The results indicate that organizational factors, such as work-life balance and the work environment, are the most consistent influences on employee engagement, whereas leadership factors exhibit situational influences. However, the predictor variables used remain relatively constant. Therefore, future research is recommended to test other, more relevant predictors, such as OCBE, for employee engagement and to compare employee engagement with customer engagement.